Is the argentine postharvest system ready to handle more and better grains?. (September 2019) - Abadía, M.B.; Urcola, H.A.; Ferrari, M.C.; Bartosik, R.E.
Abstract: This is the first comprehensive study of the grain postharvest system of Argentina with the following objectives: 1) to group the grain elevators according to structural, technological, and insect control characteristics; 2) to analyze how the groups are positioned to take advantage of the expected increase in the country grain production; 3) to study how the different groups are positioned to adopt Best Management Practices (BMPs); and 4) to identify the main challenges of each group to implement Integrated Pest Management (IPM) programs under the new context of dichlorvos (DDVP) prohibition. A survey was conducted in 86 elevators in the main grain producing area of Argentina. Multiple correspondence and cluster analyses were used to study the relationships amongst the variables and to establish a typology of grain elevators. Three groups of facilities were identified, which mainly differed in size and grain reception capacity, turnover ratios, and fumigation modalities. Large and intermediate scale facilities emerged as the best positioned to profit the projected scenario of crop increase, because of their high reception capacity and their potential to increase the turnover ratios (these two groups handled 95% of the grain volume). Small elevators presented important constraints in their current equipment for grain reception. Large facilities appeared also as the best positioned to implement BMPs, because they would only require minor investments in aeration automation. Intermediate size facilities would also need to incorporate temperature cables for grain monitoring. BMP incorporation seems less feasible in small facilities, given the limitations in drying, aeration, and stored grain monitoring technologies. All the groups will have to make equal efforts to incorporate IPM programs after the banning of DDVP. The detection of group-specific constraints is expected to serve as an input for developing targeted technologies and more efficient sector policies. Highlights: Argentine grain elevators were discriminated based on size and technological level. Intermediate and large facilities may increase grain reception with minimum effort. Large facilities are in better position to implement BMPs. All groups must make substantial and equal efforts to implement IPM. Suitable technologies must be developed to promote improvements in small facilities.